Anti-anxiety and anti-depressive effects of Thai Mucuna pruriens seed aqueous extract against ethanol withdrawal syndrome in mice - Jirayut Kaewmor; Sirinapa Rungruang; Kutcharin Phunikhom; Jintana Sattayasai; Charshawn Lahnwong (Elsevier, 2024)
Background: Thai Mucuna pruriens (T-MP) has been used as a traditional medicine for treating many neurological conditions due to its antioxidant and neurorestorative properties. Aim of the study: This study was to explore the effects of T-MP seed extract on ethanol withdrawal syndrome (EWS) in mice. Methods: Mice were administered either normal saline solution (NSS) or 2 g/kg of 20% ethanol intraperitoneally once daily for 10 days. Behavioral symptoms of EWS were evaluated at 12-, 24-, and 36-hours after the last dose of ethanol using the elevated plus maze (EPM), light-dark box (LDB), and tail suspension test (TST). After determining the best time interval to detect EWS, a new set of mice were induced to have EWS, at 23 h after the last ethanol dose, mice were treated with either NSS (PO), diazepam (4 mg/kg, IP), or T-MP seed extract (600 mg/kg, PO). Behavioral tests were conducted one hour after treatment. Results: In the ethanol withdrawal mice, anxiety- and depressive-like behavior representing EWS were seen in LDB, EPM and TST, especially at the 24-hour after the final ethanol dose. At 36-hour after the final ethanol dose, although the anxiety-like behavior could be seen in LDB and EPM, whereas no significant depressive-like in TST was observed. Treatment with DZP or T-MP could significantly reduce the anxiety- and depressive-like symptoms of EWS at 24-hour after last dose of ethanol. In addition, treatment with T-MP, but not DZP, significantly reduced the total immobility time when compared to the control ethanol withdrawal group. Conclusion: According to this study, it was discovered that T-MP seed extract could potentially offer a beneficial effect in managing anxiety- and depression-like behaviors in EWS in mice.